Climate risk country profile Cambodia. (Climate risk country profiles., 2021)
It outlines rapid onset and long term changes in key climate parameters, as well as the impact of these changes on communities, livelihoods, and economies many of which are already underway. The publication is part of a series of climate risk country profiles published jointly by ADB and the World Bank Group. The aim of the series is to provide development practitioners with easy to use technical resources to facilitate upstream country diagnostics, policy dialogue, and strategic planning.